Anisotropic MOF-on-MOF Growth of Isostructural Multilayer Metal–Organic Framework Heterostructures - Zhida Gu; Wenlei Zhang; Ting Pan; Yu Shen; Peishan Qin; Peng Zhang; Xiaohan Li; Liwei Liu; Linjie Li; Yu Fu; Weina Zhang; Fengwei Huo (Research, 2021)
Isostructural MOFs with similar crystallographic parameter are easily available for MOF-on-MOF growth and possible to form core–shell structure by isotropic growth. However, due to well-matched cell lattice, selective growth in isostructural MOF heterostructures remains a great challenge for engineering atypical MOF heterostructures. Herein, an anisotropic MOF-on-MOF growth strategy was developed to structure a range of multilayer sandwich-like ZIF-L heterostructures via stacking isostructural ZIF-L-Zn and ZIF-L-Co alternately with three-, five-, seven-, and more layer structures. Moreover, these heterostructures with highly designable feature were fantastic precursors for fabricating derivatives with tunable magnetic and catalytic properties. Such strategy explores a novel way of achieving anisotropic MOF-on-MOF growth between isostructural MOFs and opens up new horizons for regulating the properties by MOF modular assembly in versatile functional nanocomposites.